KEBIJAKAN HUKUM PIDANA PENGGUNAAN MOTIF DALAM SISTEM PEMIDANAAN - Damiri Damiri (KEADILAN PROGRESIF, 2019)
The public's reaction to law and crime often questions the motives of the perpetrator when committing a crimeor violation of the law. The problem is how the use of Motives in proving the Elements of Criminal Actions andErrors is related to Intentional elements and elements with the Intent in criminal acts. The approach methodused is a normative juridical approach, data sourced from literature studies and data analysis is carried outqualitatively. The results of the study prove that the use of Motives in proving the Elements of Crime and Errorsis related to the intentional element that exists in a criminal act. The use of motives to prove the element ofcrime and errors is shown in the Decision of the South Jakarta District Court No. No. 1488 / Pid.B / 2008 /PN.Jkt.Sel. in the case of Munir's murder with defendant Muchdi Purwo prajono. New motives can be proven ifit is related to the actions and actions taken by the defendant. The use in this way, basically wants to prove theintentional element of the criminal act being charged. While the motive in the policy of applying criminal law isone of the factors considered in determining the size of criminal law. As a suggestion at the application policylevel, finding the motive for committing a crime means knowing the meaning of the deed for the offender. This isin line with the criminal law renewal policy which emphasizes not only actions, but also the emphasis on peoplewho commit criminal acts.